2021
DOI: 10.1002/chem.202101132
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Hydroboration of Alkynes

Abstract: Herein we reported the electrochemical hydroboration of alkynes by using B2Pin2 as the boron source. This unprecedented reaction manifold was applied to a broad range of alkynes, giving the hydroboration products in good to excellent yields without the need of a metal catalyst or a hydride source. This transformation relied on the possible electrochemical oxidation of an in situ formed borate. This anodic oxidation performed in an undivided cell allowed the formation of a putative boryl radical, which reacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 75 publications
1
24
0
Order By: Relevance
“…Finally, the target syn ‐hydroborated product is released in the presence of ethanol as a hydrogen donor reagent. Very recently, a metal‐catalyst free electrochemical hydroboration of terminal alkyne was reported by Jubault and Poisson et al (Scheme 26c) [100] . The use of n Bu 4 NBF 4 as an electrolyte in MeOH, stainless steel electrodes (SSE) at both cathode and anode with a current of 10 mA and a total charge of 2 F.mol −1 were crucial for achieving exclusive syn ‐hydroborated product in excellent yield.…”
Section: Syn‐hydroboration Of Alkynesmentioning
confidence: 99%
“…Finally, the target syn ‐hydroborated product is released in the presence of ethanol as a hydrogen donor reagent. Very recently, a metal‐catalyst free electrochemical hydroboration of terminal alkyne was reported by Jubault and Poisson et al (Scheme 26c) [100] . The use of n Bu 4 NBF 4 as an electrolyte in MeOH, stainless steel electrodes (SSE) at both cathode and anode with a current of 10 mA and a total charge of 2 F.mol −1 were crucial for achieving exclusive syn ‐hydroborated product in excellent yield.…”
Section: Syn‐hydroboration Of Alkynesmentioning
confidence: 99%
“…Based on the above control experimental results, CV data, and literature reports, 31,32 a plausible mechanism for the electrochemical hydroboration of carbonyl compounds is presented in Scheme 7. Firstly, HBpin is preferentially oxidized by a single electron transfer on the anode surface and further dissociated into a boron-centred radical (˙Bpin) and hydrogen cation (H + ).…”
Section: Resultsmentioning
confidence: 93%
“…[19][20][21][22][23][24][25][26][27][28][29][30] Nevertheless, the electrochemically catalyzed hydroboration has been rarely reported to form the corresponding boronates. 31,32 Quite recently, Qing et al reported the electrocatalytic hydroboration of aryl alkenes with HBpin; however, an additional 0.8 equivalents of N,N-diisopropylethylamine as an additive was required to promote the formation of products. 31 To our surprise, no example of electrochemical hydroboration of carbonyl compounds has been reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…Among these reported methods for the preparation of organoboron compounds, hydroboration reactions employing HBpin as the boron source are one of the most common methods. Hydroboration of internal or terminal alkynes is already one of the well-established strategies for the construction of alkenyl boron compounds. Meanwhile, dehydrogenative borylation of terminal alkynes is also an attractive coupling route that furnishes a variety of alkynyl boron compounds …”
Section: Introductionmentioning
confidence: 99%